An optimal control approach to steam distillation of essential oils from aromatic plants. (2nd September 2018) - Valderrama, F.; Ruiz, F.
Highlights: A novel multi-objective optimal control of oil essentials extraction. Yield maximization and energy reduction are simultaneously attained. Time-variant steam flow trajectories are found as optimal solutions. Optimal solutions change slightly with parameters of the vegetable material. Abstract: In this work, an optimal steam flow trajectory for essential oils extraction from aromatic plants is derived, minimizing energy consumption. A phenomenological dynamic model of the oil extraction process is adopted from literature and a multi-objective optimal control problem is formulated, in order to minimize energy consumption and at the same time maximize the yield of extraction. The resulting optimal control problem is highly non-linear and it is solved by numerical methods. Simulation results are presented for three scenarios: (i) Maximum yield, (ii) minimum energy consumption and (iii) trade-off between yield and energy. It is shown that the optimal steam flow rate trajectory is not necessarily constant. Using a mixed cost-function, it is possible to extract almost 100% of oil essential while saving 60% of energy. Finally, a sensitivity analysis shows that the optimal steam trajectory has few variations when parameters of the plant physiology change.